The Analytics of the Pro-poorness of Zambia’s Economic Growth - Filakati, Ian C. (Current Aspects in Business, Economics and Finance Vol. 5, 2022)
Economic growth and its effect on economies and citizens have been widely debated by economists for some time, with one of its key characteristics being that the benefits of such growth trickle down to all sections of society, particularly the poor. This trickle-down hypothesis has recently been called into question, with prominent authors proposing a pro-poor measure of economic growth. Poverty is one of the major problems affecting a large proportion of the population in Zambia. This research empirically measures the pro-poorness of economic growth in Zambia from 2006 to 2015 while keeping track of surveys from 2006, 2010, and 2015. Based on the poverty equivalent growth rate criteria, we discover that Zambia's economic growth has not been favourable to the poor. Even while Zambia saw positive economic growth during this time and poverty rates slowly decreased, the poor received proportionately less benefit from this growth than the non-poor. The poor have not been significantly touched by growth, which necessitates a thorough analysis of the poor's demographic makeup and possible contributions to economic growth in order to effectively create interventions that will benefit this population in terms of poverty reduction.